The Role of Nicotinic Anti-Inflammatory Pathway in Prostaglandin Mediated Inflammatory Response in Sepsis: A Short Review - Baris, Elif; Arici, Mualla Aylin; Hamurtekin, Emre (Marmara Univ, Inst Health Sciences, 2019)
Sepsis is a severe and multifaceted condition of body in response to an infection, which affects multiple organs systems that makes it difficult to treat and enhances the mortality rates. Release of inflammatory cytokines can initiate an inflammatory response during sepsis. However, the response can be modified by the control mechanism inside the body that are essential for the keeping the balance and survival. The cholinergic anti-inflammatory pathway is defined as a comprehensive neurohumoral pathway that diminishes pro-inflammatory cytokine release through the vagus nerve and cholinergic receptors, predominantly alpha 7 nicotinic acetylcholine receptors (alpha 7nAChR) that expressed on inflammatory mononuclear cells. Thus, cholinergic agonists might be a part of prospective treatment approach in inflammatory diseases such as sepsis. This review covers the role of cholinergic system in prostaglandin mediated inflammatory response.
Keywords: Cholinergic anti-Inflammatory pathway; alpha 7nAChR; inflammation; sepsis; prostaglandin